Expectativas y experiencias de uso de las mujeres gitanas mayores ante los servicios sanitarios de atención primaria - Ramos-Morcillo, Antonio Jesús (Aten Primaria, 2015)
OBJECTIVE: To know the expectations and user experiences of older Roma women with health services in primary care (PC). DESIGN: Phenomenological qualitative study. Using focus groups (4-9 women/group) and semistructured interviews. Audio recorded from March to November 2011. LOCATION: Performed in Úbeda and Linares (Spain). PARTICIPANTS AND SETTING: Roma women over 50 years. A purposive sample stratified by age and area of residence was carried out. Woman were recruited through community leaders. METHOD: Process of qualitative content analysis: coding, triangulation, obtain and verify results. Supported whit the software Nvivo 8. RESULTS: Three focus groups and four interviews were conducted, including 23 women. The expectations for the PC are focus exclusively on their physician, being invisible other professionals. They look for a relationship with their physician based on trust. In their user experience with the PC coexist three types of user: who goes to their appointments, demands attention only in acute disease and does not attend appointments and reviews. There are socio-cultural factors related to accessibility. CONCLUSIONS: Older Roma women set their expectations and experiences with health service in PC around the binomial disease/physician. Expect attention based on trust and a high instrumentalization. A speech with signs of change directed towards a more active and demanding participation in PC services is observed.